2012
DOI: 10.1038/onc.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

The critical roles of endoplasmic reticulum chaperones and unfolded protein response in tumorigenesis and anticancer therapies

Abstract: Cancer progression is characterized by rapidly proliferating cancer cells that are in need of increased protein synthesis. Therefore, enhanced endoplasmic reticulum (ER) activity is required to facilitate the folding, assembly and transportation of membrane and secretory proteins. These functions are carried out by ER chaperones. It is now becoming clear that the ER chaperones have critical functions outside of simply facilitating protein folding. For example, cancer progression requires GRP78 for cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
491
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(505 citation statements)
references
References 184 publications
(254 reference statements)
4
491
0
10
Order By: Relevance
“…Pieces were placed in 30 mM EDTA/PBS for 30 min, passed through a 100-µm cell strainer, and centrifuged, RNA was isolated from crypts, and RT-qPCR was performed as described below. (Luo and Lee, 2013); Xbp1-deficient tumor cells exhibit impaired growth when xenografted into Scid mice (RomeroRamirez et al, 2004(RomeroRamirez et al, , 2009, and disruption of Ire1/Xbp1 signaling may be exploited pharmacologically for the treatment of multiple myeloma (Lee et al, 2003;Mimura et al, 2012). Our data imply an unexpected tumor-preventive role of Xbp1 in the intestinal epithelium.…”
Section: Methodsmentioning
confidence: 66%
See 2 more Smart Citations
“…Pieces were placed in 30 mM EDTA/PBS for 30 min, passed through a 100-µm cell strainer, and centrifuged, RNA was isolated from crypts, and RT-qPCR was performed as described below. (Luo and Lee, 2013); Xbp1-deficient tumor cells exhibit impaired growth when xenografted into Scid mice (RomeroRamirez et al, 2004(RomeroRamirez et al, , 2009, and disruption of Ire1/Xbp1 signaling may be exploited pharmacologically for the treatment of multiple myeloma (Lee et al, 2003;Mimura et al, 2012). Our data imply an unexpected tumor-preventive role of Xbp1 in the intestinal epithelium.…”
Section: Methodsmentioning
confidence: 66%
“…Human tumor cells indeed exhibit evidence of ER stress, and reduced capacity to elicit an UPR within malignant cells results in decreased tumorigenesis in model systems (Ma and Hendershot, 2004;Bi et al, 2005;Fu et al, 2008;Luo and Lee, 2013). Xbp1 has been considered protumorigenic sustained, augments tumor formation in both an inflammatory (i.e., CAC after DSS/AOM) and noninflammatory (i.e., CRC in Apc min mice) context.…”
Section: Isc Expansion Is Individually Determined In Each Xbp1-deficimentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction has also been detected in a yeast 2-hybrid screen (Li, et al 2012). Because an important function of GRP78 is as an endoplasmic reticulum chaperone, coordinating the cellular response to protein misfolding (Luo and Lee 2013), the involvement of IGFBP-3 in this process was sought, but IGFBP-3 was not implicated in any pathway of unfolded protein response signaling (Grkovic et al 2013). GRP78 has also been shown to be required for stress-induced autophagy , and an investigation of the possible role for the IGFBP-3-GRP78 interaction in this process in breast cancer cells revealed that IGFBP-3 could enhance the survival of cells subjected to glucose starvation and hypoxia in a GRP78-dependent manner (Grkovic et al 2013).…”
Section: Grp78 and Autophagymentioning
confidence: 99%
“…The UPR plays important roles in tumorigenesis, therapy resistance, and cancer progression (14,32). Moderate and transient UPR activation by E 2 and other activators promotes an adaptive stress response, which increases UPR expression and confers protection from subsequent exposure to higher levels of cell stress (14,33).…”
Section: Bhpi Rapidly Depletes Intracellular Atp Stores and Activatesmentioning
confidence: 99%